Monitoring Quality of Mafia‐Connected Accountants - Bianchi, Pietro A.; Francis, Jere R.; Marra, Antonio; Pecchiari, Nicola (Journal of Accounting Research, 2026)
ABSTRACT We investigate the monitoring quality of accountants with ties to the Mafia in their role as auditors for “clean” firms—those with no known ties to organized crime. Using a proprietary government database, we identify Italian firms with alleged ties to the Mafia through their executives, directors, or shareholders. We define “suspect accountants” as those who serve as auditors for these Mafia‐connected firms, acknowledging their potential associations with criminal entities. We predict and find evidence that “clean” clients (treatment group) monitored by suspect accountants are more likely to engage in earnings management practices that reduce taxable income, compared with a control sample of “clean” firms monitored by accountants with no known Mafia ties (control group). Our findings suggest that accountants with ties to the Mafia act as low‐quality monitors in the “clean” economy.